2009
DOI: 10.1111/j.1439-0272.1998.tb02827.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different uropathogenic microorganisms on human sperm motility parameters in an in vitro experiment

Abstract: Summary. The influence of different uropathogenic microorganisms (E. coli, enterococcus, Pseudomonas aeruginosa, Staphylococcus saprophyticus, Candida albicans) on human sperm motility was studied in vitro with a computer‐assisted sperm analyser (CASA). Native ejaculates were prepared with the swim‐up technique and adjusted to 22 times 106 spermatozoa ml−1. The sperm suspension was artificially infected with microorganisms in concentrations varying from 2 times 103 to 2 times 107. Sperm motility was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 14 publications
4
49
1
2
Order By: Relevance
“…An inhibitory effect of E. coli, serotype 06, on sperm motility has been investigated by some authors (105). Sperm incubated with E. coli demonstrated significant alterations in motility (78,106). Some investigators revealed that the immobilization of spermatozoa may occur as a result of direct contact of the sperm with bacterial cells (105,107).…”
Section: Escherichia Colimentioning
confidence: 99%
See 1 more Smart Citation
“…An inhibitory effect of E. coli, serotype 06, on sperm motility has been investigated by some authors (105). Sperm incubated with E. coli demonstrated significant alterations in motility (78,106). Some investigators revealed that the immobilization of spermatozoa may occur as a result of direct contact of the sperm with bacterial cells (105,107).…”
Section: Escherichia Colimentioning
confidence: 99%
“…E. coli has a passive effect on sperm motility and acrosomal function (48). Several authors were described spermagglutination and immobilization by E. coli (52,78).…”
Section: The Effects Of Bacterial Infection On Sperm Parametersmentioning
confidence: 99%
“…İnfeksiyon sonucu ortaya çıkan lökospermide, lökosit ve lökosit ürünlerinin spermler üzerine toksik etki yaparak fertilizasyonu olumsuz yönde etkilediği bildirilmiştir [3]. Benzer şekilde, mikroorganizmalar veya immün hücrelerin sperm hücreleri üzerine olumsuz etkilerinin olabileceği, bir olasılık olarak ileri sürülmektedir [4]. Erkek infertilitesinin %15'inde üreme yolları infeksiyonlarının sorumlu olduğu ileri sürülmektedir [5].…”
Section: Giriş Ve Amaçunclassified
“…There are several in vivo as well as in vitro studies showing a negative effect of E. coli on human sperm function such as motility and acrosome reaction (Auroux et al, 1991;Merino et al, 1995;el-Mulla et al, 1996;Huwe et al, 1998;Kohn et al, 1998;Diemer et al, 2003). A direct inhibitory effect of E. coli on progressive motility was found to depend on bacterial concentration, and analysis by electron microscopy revealed multiple adhesions of E. coli to spermatozoa with a variable degree of ultrastructural damage present (Diemer et al, 1996).…”
Section: Impairment Of Testicular and Sperm Function By E Colimentioning
confidence: 99%